Structural and functional characterisation of chikungunya virus replication complex dynamics - Tan, Yaw Bia (Nanyang Technological University, 2019)
Chikungunya virus (CHIKV) is a 12 kilobase (kb) positive sense single strand RNA (+ssRNA) mosquito-borne virus. Through mosquito bites, the infected victims develop Chikungunya Fever (CHIKF) associated with symptoms like acute fever and painful polyarthritis. Unfortunately, there are no current effective antiviral drugs and vaccine treatments against CHIKV and many other +ssRNA viruses due to the inadequacy of biological information of its replication complex (RC) formations and the process of viral replications. Hence, this project aims to provide the structural and functional characterisation of the replication dynamics of CHIKV RC, made of 4 non-transmembrane non-structural proteins (nsPs; nsP1-4) contributing their enzymatic activities essential to viral replication. Recombinant CHIKV RC bound to its binding partners, such as 3’ untranslated region (UTR) region of viral RNA, was reconstituted in vitro for its macromolecular 3D modelling and analysis through Electron Microscopy (EM). A quick and convenient bacterial cell-based luciferase system to study the CHIKV replication dynamics was established. The detection of the signal amplification of the Renilla Luciferase (Rluc) luminescence indicated the presence of viral replication activity from the replicase plasmid expressing CHIKV RC which acted on the 3’ UTR region coupled to Rluc reporter gene in the reporter plasmid. This replicase-reporter system captured the importance of selfproteolytically regulated non-structural polyprotein processing and polymerase activity of RC required for the first event of viral replication to synthesise negative-strand RNA. Further biochemical and structural determination of the enzymatic domains of CHIKV RC will reveal the functional roles and spatial organisation of nsPs in the active assembly of RC. The expansion of the experimental database will eventually build a structural-aided drug discovery platform to identify the effective antiviral drug candidates to treat the infections of CHIKV and +ssRNA group viruses.